النظام القانوني لمرفق الشرطة في التشريع الجزائري - سـايغي, حمزة; زيد, صليحة (University of Eloued جامعة الوادي, 2020)
The police is a public facility of an administrative nature for the security sector, that was built to achieve the public interest in the field of national security policy, it is used by individuals to benefit from its security activities, especially the administrative ones, also the need to balance between public order and the rights and freedom of individuals makes it necessary for Police Department to assume responsibility based on mistake or without it, as well as its activities lead to personal mistakes outside the job or the perpetrator and separate from it. The mistakes committed are a sign of bad, slow or non-functioning police facility, and there are legitimate activities that lead to personal mistakes outside that position. Also there are mistakes in the institutions caused by bad, slow or the non-operation of police facilities. Special and unusual damage to individuals, can be categorized into two cases: the use of weapons by police officers carries an exceptional risk (liability based on risk), failure to implement court rulings, lack of control over public order, or failure to implement an administrative decision (liability on the basis of equality before burdens the public).الشرطة ىي مرفؽ عا ذو طبيعة إدارية لجياز الأمف، ت إنشاؤه مف أجؿ تحقيؽ المصمحة العامة في مجاؿ سياسة أمف الدولة، والذي يستخدمو الأف ا رد للبستفادة مف نشاطو الأمني، وخاصة الإداري، والحاجة إلى التوفيؽ بيف النظا العا وحقوؽ الأف ا رد وحرياتي، تجعؿ مف الضروري تحمؿ المسؤولية عف مرفؽ الشرطة عمى أساس الخطأ أو بدوف خطأ كما أف أنشطتيا تؤدي إلى أخطاء شخصية خارج الوظيفة أو مرتكبيا ومنفصمة عنيا، وتعمؽ الأخطاء الناجمة عف سوء أو بطء أو عد عمؿ مرفؽ الشرطة، وىناؾ أنشطة مشروعة تسفر عف نتائج أنشطتيا، حيث أف أنشطتي تؤدي إلى أخطاء شخصية خارج الوظيفة أو مرتكبيا ومنفصمة عنيا ، والأخطاء في المرفقات الناجمة عف سوء أو بطء أو عد تشغيؿ م ا رفؽ الشرطة، وىناؾ أنشطة مشروعة ناتجة عف أنشطتيا. الأض ا رر الخاصة وغير العادية للؤف ا رد، والتي في حالتيف: استخدا الأسمحة مف قبؿ ضباط الشرطة تنطوي عمى مخاطر استثنائية )مسؤولة عمى أساس المخاطر(، وعد تنفيذ الأحكا القضائية، وعد السيطرة عمى النظا العا، أو عد تطبيؽ ق ا رر إداري )المسؤولية عمى أساس المساواة قبؿ الأعباء العامة(. يجوز لمطرؼ المصاب المجوء إلى السمطات القضائية في إطار المطالبة بالمسؤولية الإدارية لمتابعة المرفؽ والحصوؿ عمى تعويض.
مذكرة ماستر
Keywords: Police, weapons, hazards.; الشرطة .الاسلحة .المخاطر